EFFECT OF WOUND TREATMENT WITH PSYCHONEUROIMUNOLOGICAL (PNI) APPROACH TO IMPROVEMENT OF DIABETES MELLITUS WOUND GRADE - Sufendi Hariyanto; Kristian Dwi Mulyanto; Kurniawati Kurniawati; Ade Armada (Bajang Institute, 2022)
Diabetes Mellitus is a heterogeneous disorder that causes microvascular damage resulting in scarring of the peripheral tissues. Diabetic wounds are chronic so that they affect the quality of life. Appropriate wound care can speed up the healing process. The aim of this study was to determine the effect of wound care using a psychoneuroimmunological approach to improving wound grade. The research was conducted in the wound care clinic at Mojowarno Christian Hospital from 19 October to 16 November 2020. Using a designquasy experience.The population is all wound care clinic patients. The research sample uses the techniquetotal sampling a total of 28 respondents, divided into 14 respondents in the treatment group (with a psychoneuroimmunology approach) and 14 respondents in the control group (according to the SPO). Researchers used observation sheets that were carried out for 2 weeks of treatment. Research shows that almost all wound care with a psychoneuroimmunology approach has improved wound grade compared to wound care according to SPO. The Wilcoxon test for the treatment group ƿ=0.001 (ƿ<α 0.05), means that there is an improvement. Control group Wilcoxon test ƿ=0.083 (ƿ>α 0.05), meaning there is no improvement. Mann Whitney test ƿ=0.029 (ƿ>α 0.05), meaning that there is an effect of wound care with a psychoneuroimmunology approach on improving the grade of diabetes mellitus wounds. The results of the study showed that there was an effect of wound care with a psychoneuroimmunological approach to improving the grade of diabetes mellitus wounds. It is recommended for hospitals to use wound care methods with a psychoneuroimmunology approach so that the wound healing process is faster.